OPTIMALISASI RETURN ON ASSET (ROA) DAN RETURN ON EQUITY (ROE) UNTUK MENINGKATKAN DAYA SAING PERBANKAN DI BURSA SAHAM - Nugroho, Wijil; Silaen, Montaris; Parhusip, Arisman; Al-Amin, Al-Amin (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2024)
In the competitive stock market dynamics, banks are always looking for strategies to improve their advantages. This study aims to investigate the importance of Return on Asset (ROA) and Return on Equity (ROE) in increasing banking competitiveness on the stock exchange. Using the literature review method, this study collects and reviews various relevant literature to identify and analyze the relationship between ROA, ROE and bank stock performance. The results of this study show that ROA and ROE have direct implications on how investors value banks. Banks that demonstrate high operational efficiency and good capital management capabilities often score higher in the eyes of investors. This is because good ROA and ROE reflect effective asset and capital management, which is critical to long-term profit sustainability. A high ROA indicates that the bank is able to maximize the return on its assets, while a high ROE indicates the bank's ability to generate value for shareholders from the funds they invest. This research reinforces the understanding that ROA and ROE optimization is not only about increasing profits, but also about building and maintaining investor trust and market reputation. Thus, banks should prioritize effective management of their assets and capital as part of their strategy to increase competitiveness in the stock market. This conclusion encourages the banking sector to focus more on financial-strategies that can increase ROA and ROE values in order to strengthen their position in this highly competitive stock market.